Comparability of Cash Flow Statements: Evidence from Baltic Countries - Vaiva Kiaupaite-Grusniene; Lehte Alver (Journal of Accounting and Management Information Systems (JAMIS), 2019)
Research Question: Whether the adoption of IFRSs has led to the harmonization and comparability of Baltic listed companies' cash flow statements? Motivation: Baker and Barbu (2007) have marked that the adoption of IFRSs in EU is the new phase of international harmonization. However, IFRSs still provide flexibility to financial statement preparers when applying the standards due to explicit options, discretion in interpretation and the need for estimates (Wehrfritz & Haller, 2014). Measuring the extent to which financial reports of companies are comparable is an important topic. Our research applies H-index and C-index for measuring harmonization of Baltic listed companies' cash flow statements. Idea: We examine the problem of harmonization cash flow statements. Data: The sample contains all companies (in total 33) listed on Nasdaq Baltic market for years 2010–2017. Tools: To measure harmonization and comparability of financial reports H-index for each country was found. C-index was used for finding overall, within-country and between-country harmonization. Findings: While there is a longitudinal consistency in classification choice within each company, there is no consistency among the companies in interest received and paid. Dividend treatment is more consistent and harmonized. Users of financial reports should not expect comparability of cash flow statements of Estonian, Latvian and Lithuanian companies, despite the existence of a single stock exchange, cross-border cultural and economic similarities and de jure harmonization of accounting standards. Contribution: This paper contributes to IFRSs impact analysis, and specifically harmonization and comparability literature, by providing comparative results for Estonia, Latvia and Lithuania in financial statement preparers' classification judgement.
Keywords: M40; M41; M48; G14; 650; accounting; IFRS; accounting policy choice; classification; cash flow